2021
DOI: 10.1038/s41598-021-89165-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pore diameter on the elution behavior of analytes from thermoresponsive polymer grafted beads packed columns

Abstract: Temperature-responsive chromatography using thermoresponsive polymers is innovative and can control analyte retention via column temperature. Analyte elution behavior in this type of chromatography depends on the modified thermoresponsive polymer and the structure of the base materials. In the present study, we examine the effect of the pore diameter of silica beads on analyte elution behavior in temperature-responsive chromatography. Poly(N-isopropylacrylamide-co-n-butyl methacrylate) hydrogel was applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Phenobarbital has a benzene ring adjacent to the amide bond, which interacts with PNIPAAm through hydrophobic interactions in addition to hydrogen bonding. In a previous report on temperature-responsive chromatography, phenobarbital exhibited a relatively longer retention time compared to other types of barbiturates with similar structures, barbital and allobarbital 47 . This also indicated that the phenobarbital structure caused specific retention on the PNIPAAm column.…”
Section: Resultsmentioning
confidence: 82%
“…Phenobarbital has a benzene ring adjacent to the amide bond, which interacts with PNIPAAm through hydrophobic interactions in addition to hydrogen bonding. In a previous report on temperature-responsive chromatography, phenobarbital exhibited a relatively longer retention time compared to other types of barbiturates with similar structures, barbital and allobarbital 47 . This also indicated that the phenobarbital structure caused specific retention on the PNIPAAm column.…”
Section: Resultsmentioning
confidence: 82%
“…Thus, the diffusion of the steroids into the thicker PNIPAAm hydrogel layer resulted in a slower elution from the beads and wider peaks in the chromatogram. Previous studies have suggested that small molecular analytes tend to diffuse into a thick PNIPAAm layer composed of large molecular weight PNIPAAm on silica beads at a higher temperature 44 , 47 50 .
Figure 3 Chromatograms of hydrophobic steroids using crosslinked PNIPAAm modified-bead packed columns using beads prepared via polymerization for ( A ) 5 h, and ( B ) 18 h. The mobile phase was pure water.
…”
Section: Resultsmentioning
confidence: 99%
“…Since the phase transition temperature is close to the body temperature, PNIPAAm has been used in various biomedical applications such as temperature-modulated drug and gene delivery systems 10 15 , biosensors and bioimaging systems utilizing the phase transition properties of PNIPAAm 16 21 , cell separation systems using the difference in cell adhesive properties among cells on PNIPAAm 22 30 , and cell culture substrates for tissue engineering using temperature-modulated cell adhesion and detachment 31 38 . When applied to chromatography, PNIPAAm-modified silica beads are used as the stationary phase 39 44 . Because the hydrophobicity of PNIPAAm changes according to the external temperature, the hydrophobic interaction between PNIPAAm and the analyte can be modulated by changing the column temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The bead suspension was poured into the reservoir of the column packer that was connected to an empty column 44 . Beads were packed to enable a continuous flow of a mixed solvent with a continuous pressure of 350 kg/cm 2 for 1 h 43 . Then, the column was connected to a high-performance liquid chromatography system (Chromaster, Hitachi High-Tech Science, Tokyo, Japan), which was rinsed with pure water flowing at 1.0 mL/min at 40 °C for 5 h.…”
Section: Methodsmentioning
confidence: 99%
“…The retention factor, k ′, was obtained using Eq. ( 4 ) as follows: where t R is the retention time of the analyte and t 0 is the retention time of uracil as an initial standard 43 . Oligonucleotides were used as a sample for nucleic acid medicine 66 .…”
Section: Methodsmentioning
confidence: 99%